Workers’/Affordable Housing and the Development of Construction Systems. - McGuinness, John (Industrial Archaeology Review, 2017)
Whether motivated by commercial or social forces, the provision of housing for the working/labouring classes has required a balance between providing housing of a satisfactory standard and the cost which, while generating a rent affordable to the people for whom the houses were intended, gave a reasonable return on the investment made by the developer. This paper gives an introduction to the history of this branch of the building industry and describes by way of surviving building examples the ways in which the industry sought to reduce costs of both labour and materials. Focusing on the first half of the 20th century, the article discusses surviving examples of affordable construction designs, from the Cheap Cottages Exhibition at Letchworth Garden City in 1905 and the experimental system build housing in the 1920s and 1930s which often used concrete to immediate post-Second World War mass house-building designs.